Efficient Fill-Level Monitoring for Smart E-waste Recycling - Low, Sze Yen; Ooi, Shih Yin; Cham, Chin Leei; Kwan, Wei Peng; Pang, Ying Han; Tneo, Jia Er; Ong, Kah Ming (International Journal of Membrane Science and Technology, 2023)
Proper electronic waste management is compulsory nowadays because, with improper management, the harmful substances in electronic waste will put humans and the environment at risk. The production of e-waste differs from domestic waste as it is not regular. It is vital to improve the e-waste management process. This paper presents a smart e-waste bin fill level monitoring system. This paper proposes a module for identifying fill level, display, and communication systems integrated with a mobile application. Different sensors are implemented to monitor the bin status in real-time. The system will alert the collection party on various scenarios through a mobile application, including the full bin and a fire in the container.